A compound interpolation envelope local mean decomposition and its application for fault diagnosis of reciprocating compressors. (15th September 2018) - Haiyang, Zhao; Jindong, Wang; Lee, Jay; Ying, Li
Highlights: MPCHI envelope performances well in nonstationary part of a signal. CSI envelope is more suitable in the smooth part of a signal. A CIE LMD method based on MPCHI and CSI was proposed. The CIE LMD performances better for the diagnosis of reciprocating compressor bearing fault. Abstract: Local mean decomposition (LMD) is a self-adaptive analysis method which can decompose a signal into a set of product function (PF) components, and the construction of envelope function plays an important role in the accuracy of its PF components. According to the local nonstationary characteristics of vibration signals, a compound interpolation envelope (CIE) LMD was proposed through a novel envelope construction method. By defining an nonstationary coefficient to evaluate the local nonstationary characteristics of vibration signals, an compound envelope construction method which use Monotonic Piecewise Cubic Hermite Interpolation (MPCHI) for nonstationary part and Cubic spline interpolation (CSI) for smooth part was proposed, and an CIE LMD algorithm was give based on the novel envelope construction method. A numerical example simulation was conducted to verify the performance of CIE LMD, results indicated that CIE LMD outperforms three other methods. The CIE LMD was employed to diagnose the oversized bearing clearance fault in reciprocating compressor, and the envelope frequency spectrum of PF component gives a more significant peak of fault frequency than that of original signal, which further indicates that this proposed method is competent for the diagnosis of reciprocating compressor oversized bearing clearance fault.